Evaluasi Sekolah Lapang Sistem Tanam Padi Jajar Legowo Super dengan Metode Tyler - Khaerunnisa; Reni Suryanti (Politeknik Pembangunan Pertanian Bogor, 2020)
Field school is one of the extension approaches to disseminate technology in rice cultivation. Evaluation of field schools can be done by using the Tyler method. The objectives of this study were (1) to analyze the understanding of farmers (knowledge, attitudes and skills) in implementing the cultivation of jajar legowo super systems of rice; (2) identify the achievement of extension in field school. The results showed that the farmers' knowledge, attitudes and skills were at moderate to high levels. Evaluation using the Tyler model shows that the objectives of the outreach activity through field schools have been achieved. Keywords: jarwo super, field school, evaluation of extension